The Maslahah of Muslim Consumer Behavior in Using E-Wallet in Makassar City - Nurjannah Nurjannah; Irwan Misbach; Rahmawati Muin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
Technological developments affect the changes in a person's consumption level. The existence of a non-cash payment method using an e-Wallet that provides various conveniences is undeniably a disadvantage for its users, especially Muslim consumers; one of them is a wasteful attitude. Wasteful or consumptive behavior is an act prohibited in Islam. This study aimed to reveal and explain the maslahah of Muslim consumer behavior in using e-Wallet. This study was qualitative with a phenomenological approach. The primary data sources came from interviews conducted with e-Wallet users of OVO, GoPay, DANA, ShopeePay, and LinkAja types in Makassar City aged 21-35 and had worked. Additionally, the secondary data sources came from various references, such as books, journals, and other research. The data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The study results indicated that the maslahah of Muslim consumer behavior in Makassar City using e-Wallet was practical in transacting; safe and clean in transactions, save on shopping and be more diligent in a donation. The use of e-Wallet can be categorized at the level of maslahah hajiyyah, whose existence can help the difficulties faced by Muslim consumers.